2019
DOI: 10.14814/phy2.14057
|View full text |Cite
|
Sign up to set email alerts
|

Sympathoexcitation and impaired arterial baroreflex sensitivity are linked to vascular inflammation in individuals with elevated resting blood pressure

Abstract: Elevated Resting Blood Pressure ( ERBP ) in the prehypertensive range is associated with increased risk of hypertension and cardiovascular disease, the mechanisms of which remain unclear. Prior studies have suggested that ERBP may be associated with overactivation and dysregulation of the sympathetic nervous system ( SNS ). We hypothesized that compared to normotensives (≤120/80 mmHg), ERBP (120/80–139/89 mmHg) has high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Given recent reports linking inflammation, MSNA and BRS (Fonkoue et al, 2019), we also explored the link between PTSD symptom severity and inflammation. Chronic inflammation could contribute mechanistically to BRS dysfunction via its direct effect on the vasculature, compromising the baroreceptor nerve endings or affecting its afferent and efferent tracts in the central nervous system prior to the development of hypertension (Chapleau et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Given recent reports linking inflammation, MSNA and BRS (Fonkoue et al, 2019), we also explored the link between PTSD symptom severity and inflammation. Chronic inflammation could contribute mechanistically to BRS dysfunction via its direct effect on the vasculature, compromising the baroreceptor nerve endings or affecting its afferent and efferent tracts in the central nervous system prior to the development of hypertension (Chapleau et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed an increased sympathetic activity in obese subjects, as assessed by direct recordings of muscle sympathetic nerve activity (MSNA) [56,57,58,59,60]. Grassi et al showed that both heart rate and MSNA baroreflex changes were attenuated in hypertensive obese subjects compared to normotensive subjects.…”
Section: Mechanisms Linking Obesity To Hypertensionmentioning
confidence: 99%
“…BEI, baroreflex effectiveness index; BRS, baroreflex sensitivity; HUT, head up tilt. Fonkoue et al, 2019;Lázaro et al, 2019;Simpson et al, 2019;Wakeham et al, 2019). Continuously and non-invasively measured peripheral BP was demonstrated to give a good approximation of intra-arterial radial BP in different clinical populations (Pinna et al, 2000;Ameloot et al, 2014;Smolle et al, 2015;Berkelmans et al, 2017).…”
Section: Accuracy Of the Bp Measurements Used As A Gold Standardmentioning
confidence: 99%